Gustatory and olfactory function in patients with granulomatosis with polyangiitis (Wegener's). (November 2014) - Proft, F; Steinbach, S; Dechant, C; Witt, M; Reindl, C; Schulz, S; Vielhauer, V; Hilge, R; Laubender, RP; Manger, K; Nüsslein, H; Wendler, J; et al.
<x xml:space="preserve">Abstract</x> Objectives: Recent findings suggest that autoimmune disorders predispose to a diminished capacity to taste and smell. This has been shown for patients with systemic lupus erythematosus as well as for patients with rheumatoid arthritis (RA). Granulomatosis with polyangiitis (GPA), with its particular manifestations in the upper respiratory tract, may therefore have an even higher impact on these senses. The aims of this study were to evaluate the gustatory and olfactory function in patients with GPA, to compare them to sex- and age-matched healthy controls, and to correlate these findings with their GPA disease severity. Method: Patients with established GPA were analysed by standardized assessments for gustatory and olfactory functions and examined for disease activity, stage of disease, and treatment. Results: Forty-four GPA patients were tested for their chemosensory functions. Compared to age- and sex-matched healthy controls, GPA patients showed significantly decreased olfactory scores along with diminished scores for their gustatory functions. The diminished sense of smell in GPA patients correlated significantly with elevated C-reactive protein (CRP) values whereas the gustatory impairment correlated with the duration and extent of the disease. Conclusions: Our results indicate that olfactory and gustatory functions are significantly decreased in GPA. As the olfactory function of these patients was comparable to patients with RA, chemosensory impairment may not simply be a consequence of the involvement of the upper respiratory tract, but rather a common complication of systemic autoimmune diseases.